The effect of spraying with amino acids on the growth of Borago Officinalis L. - محمد, حلا (Latakia University Journal -Biological Sciences Series, 2024)
The lack of information about the cultivation of borage plants in Syria increased the importance of this research, which was carried out in Tartous Governorate, Al-Rizqat area (marginal cultivation for greenhouses) for the 2023 agricultural season, to study the effect of spraying with amino acids on the growth of Borago Officinalis L., where the plants were treated with several concentrations. (0 - 0.5 - 1 - 1.5) g/l of an organic fertilizer containing 60% amino acids. The plants were sprayed several times with an interval of 20 days between one spraying and the next. The research was carried out in a randomized block design with three replicates for each treatment, in order to invest these small agricultural distances in growing plants of nutritional and medicinal importance. By comparing the averages, the results showed that there were significant differences between the studied concentrations of amino acids between them and the control, and the concentration achieved 1.5 g/ The best values were significantly superior to all concentrations and to the control in all morphological and productive characteristics of the plant (plant height - number of leaves - number of branches - number of flowers - weight of 100 seeds), where the values reached (98, 116, 21.67, 4016, 1.73). respectively.